Proceedings of the 21st International Meshing Roundtable 2013
DOI: 10.1007/978-3-642-33573-0_12
|View full text |Cite
|
Sign up to set email alerts
|

Lattice Cleaving: Conforming Tetrahedral Meshes of Multimaterial Domains with Bounded Quality

Abstract: Summary We introduce a new algorithm for generating tetrahedral meshes that conform to physical boundaries in volumetric domains consisting of multiple materials. The proposed method allows for an arbitrary number of materials, produces high-quality tetrahedral meshes with upper and lower bounds on dihedral angles, and guarantees geometric fidelity. Moreover, the method is combinatoric so its implementation enables rapid mesh construction. These meshes are structured in a way that also allows grading, in order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Combined with a clamping procedure, it was shown that small edges in the initial mesh finish expanding in as few as two to ten iterations, after which the remaining iterations are largely in improving mesh quality globally, where vertices spread apart due to the expansion factor in the rest edge length ' 0 . It may be possible to analyse convergence more rigorously to establish quality bounds, similar to [19,20,21], although such analysis would be subtle, due to the intricate coupling of edge flipping, vertex movement, and clamping. In an extensive application of the meshing algorithm in [1], tens of thousands of meshes were automatically generated and 123 successfully used in finite element methods involving coupled boundary conditions at junctions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Combined with a clamping procedure, it was shown that small edges in the initial mesh finish expanding in as few as two to ten iterations, after which the remaining iterations are largely in improving mesh quality globally, where vertices spread apart due to the expansion factor in the rest edge length ' 0 . It may be possible to analyse convergence more rigorously to establish quality bounds, similar to [19,20,21], although such analysis would be subtle, due to the intricate coupling of edge flipping, vertex movement, and clamping. In an extensive application of the meshing algorithm in [1], tens of thousands of meshes were automatically generated and 123 successfully used in finite element methods involving coupled boundary conditions at junctions.…”
Section: Discussionmentioning
confidence: 99%
“…-Volumetric meshing with guaranteed quality: Another possibility is to mesh the volumes of the individual regions/phases as a tetrahedral mesh, and then extract surface meshes from the boundaries of the volumetric meshes. In the lattice cleaving algorithm [19] (which shares aspects with the single-region isosurface stuffing algorithm of Labelle and Shewchuk [20]), a bodycentred cubic lattice is ''cleaved'', or cut, based on the approximate location of the material boundaries. In particular, vertices at the location of the cuts are ''warped'' by a procedure that guarantees mesh quality, such that minimum dihedral angles are bounded from below.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The isosurface stuffing method [17] uses a similar paradigm to represent single material domains but guarantees theoretical bounds on the tetrahedra' dihedral angles. Inspired by this strategy, Bronson et al [18] offer similar guarantees for labeled volume data.…”
Section: Introductionmentioning
confidence: 93%
“…Dey et al [2012] applied a recent Delaunay refinement algorithm to generate high quality triangular interface surfaces. Bronson et al [2013] introduced a new algorithm for generating tetrahedral meshes that conform to volumetric domains of multiple materials. Saye and Sethian [2012] extracted the multiphase interfaces with piecewise linear interpolation and further quality-improved [Saye 2013] under the framework of VIIM, which requires the continuous piecewise interpolation of every distance function and mesh abstraction and chopping.…”
Section: Interface Reconstructionmentioning
confidence: 99%